ROHINGYA, A STRUGGLE FOR RECOGNITION AS “INDIGENOUS” - Muhammad Busyairi; Thi Kim Siem Bui (Jurnal Ilmiah Kajian Keimigrasian, 2021)
Rohingya first came to Arakan State, Burma (Myanmar) between the eighth and ninth centuries. They are a Muslim minority ethnic group who have been struggling for their indigenous identity. Their arrival in Arakan correlated with the British colonialism and Japanese colonialism (1942-1945) which played a crucial role in initiating the conflicts between Muslims and Buddhists. In consideration of various definitions, Rohingya are obviously defined indigenous because they have lived in a specific territorial for long with their own language, culture and religion. This paper aims to argue that the Rohingya issue should be seen as indigenous group. To address the issue, we use a qualitative approach relying on the available secondary sources by giving historical background, theoretical framework and discussing on inter-religious conflict issue, a form of struggle for indigenous recognition. It is found that despite qualifying the standards to be admitted as indigenous, the Rohingya have been still refused to be minority ethnic group, even not accepted to be legal citizen by the Myanmar government, they are seen as foreigners or illegal immigrants instead. Three lessons are learned from this study on the failure of Rohingya’s recognition. First, the two colonialists were the “dark records” of the Rohingya conflicts. Second, the Myanmar governments have not treated the Rohingya with fair and similar policy during the historical time. Third, all protests and demonstrations conducted throughout the world to condemn the Myanmar government and all financial supports should be done on behalf of humanity, not a religious-solidarity to avoid unexpected effects for inter-religion conflicts nationally and internationally.